Correlation and Path Analysis Quantitative Character of 20 Genotype Chilli (Capsicum annuum L.): Analisis Korelasi dan Sidik Lintas Karakter Kuantitatif 20 Genotipe Cabai (Capsicum annuum L.) - Yunandra Yunandra; Muhamad Syukur; Elza Zuhry; Deviona Deviona (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2020)
ABSTRACT Chili high yield is the target of plant breeding. High yielding chili selection can be done through direct selection of yield characters and indirectly through other characters. Indirect selection is more efficient than the selection of one character. This research aims to study the relationship between quantitative characters with yield as well as obtaining the selection criteria. Correlation analysis results showed that the fruit weight, fruit diameter, pericarp thickness, leaf width, and leaf length were positively correlated and were very significant on yield. Based on the path analysis, characters that have a positive direct effect on yield are fruit weight, fruit diameter, leaf width, and leaf length, while pericarp thickness had a negative direct effect but had a large indirect effect on yield.